Achieving reading skills in a group of EFL Ecuadorian children through English phonics (Research, Society and Development, 2023)
Reading is essential to develop while learning English as a foreign language. Thus, this study focuses on aiding children to enhance reading by first teaching them letter sounds instead of letter names. The goal is to teach children how to recognize and pronounce individual letters; if they can do so, children can combine those sounds with reading. Additionally, to mitigate the interference from the sound of L1 to L2 in some English words. The method used to answer the research questions; first teaching up to three blended letter sounds to engage kids in the development of reading English with the correct pronunciation. The results demonstrate in the mean word reading (pronunciation) test that most children had improved from 5.25 to 7.79. in their score. And the errors in the same word reading pronunciation test were reduced from 4.33 to 0.285. (Std. error mean). This study suggests that teaching English letter sounds to this group of children successfully enhanced reading from an early age.